Antidiabetic activities of oil palm (Elaeis guineensis jacq.) fruit and palm oil mill effluent extracts - Sharif, Mohd Faez (2014)
Diabetes is one of the top ten causes of death in Malaysia. According to the fourth National Health and Morbidity survey conducted in 2011, it is estimated that 15.2% (2.6 million) of Malaysians adults 18 years old and above suffer from diabetes. Most antidiabetic drugs available are associated with several side effects which explain the current prevalence of diabetes. Therefore researches are needed in exploring the new alternative for antidiabetic treatment which are safe, efficient and exert a lesser amount of side effects. Recently the oil palm, Elaeis guineensis has been explored in several antidiabetic studies. The oil palm leaves have been found to reduced hyperglycemia in STZ-induced diabetic rats due to the high polyphenolic content. Nevertheless several parts of oil palm which are also contained high amount of polyphenol such as fruit and the effluent from palm oil processing, POME are never been investigated in antidiabetic study. Therefore, this study was conducted to evaluate the antidiabetic properties of oil palm fruit and POME extracts through the in vivo antihyperglycemic evaluation. In addition, an initiative was made to study the possible mechanisms involve using in vitro models. Raw POME and oil palm fruit were subjected to solvent extraction using ethanol. The extracts collected were further used in the in vivo and in vitro experiments. To evaluate the antihyperglycemic property of both extracts in diabetic rats, the rats were given the extracts orally using intragastric gavage in the in vivo study. The in vitro models were design to evaluate the potential antidiabetic mechanisms involve by using the glucose uptake, insulin secretion as well as adiponectin secretion model. The results had shown that acute treatment of POME and oil palm fruit extracts reduced fasting and postprandial hyperglycemia in streptozotocin-induced diabetic rats. Following 28-days treatment, both extracts at concentration of 500 mg kg-1 b.w significantly reduced hyperglycemia, improved the body weight and increased insulin secretion in streptozotocin induced diabetes rats. Through in vitro evaluation, the oil palm fruit extract (500μg ml-1) were found to stimulate the insulin secretion from BRIN BD11 cell line the most. Moreover both extracts also enhanced basal and insulin mediated glucose uptake into adipocytes, muscles and liver cells. In the evaluation of adiponectin secreting activity, the POME extracts significantly increased adiponectin secretion in both basal and insulin-stimulated state. However the oil palm fruit extracts significantly increased adiponectin secretion only under the insulin stimulated state. The HPLC analysis had shown the presence of gallic acid and catechin as part of the bioactive compound for both extracts. In conclusion, from in vivo evaluation the treatment of POME and oil palm fruit extracts were shown to reduce hyperglycemia at different prandial state in diabetic rats. Both extracts also did not cause severe hypoglycemia in normal rats. The in vitro study suggested that the antihyperglycemic property of POME and oil palm fruits were mediated through insulin secretion from pancreatic ß-cells, enhancement of glucose uptake by the muscles, adipocytes and liver cells and amplification of adiponectin secretion from adipocytes cells. Therefore various antihyperglycemic potential of both extracts together with its property that did not cause hypoglycemia make them suitable to be develop as new oral antidiabetic drugs.